Single-Cell Hemoprotein Diet Changes Adipose Tissue Distributions and Re-Shapes Gut Microbiota in High-Fat Diet-Induced Obese Mice - Lee, Seungki; Choi, Ahyoung; Park, Kyung Hoon; Cho, Youngjin; Yoon, Hyunjin; Kim, Pil (Journal of Microbiology and Biotechnology, 2023)
We have previously observed that feeding with single-cell hemoprotein (heme-SCP) in dogs (1 g/day for 6 days) and broiler chickens (1 ppm for 32 days) increased the proportion of lactic acid bacteria in the gut while reducing their body weights by approximately 1~2%. To define the roles of heme-SCP in modulating body weight and gut microbiota, obese C57BL/6N mice were administered varied heme-SCP concentrations (0, 0.05, and 0.5% heme-SCP in high fat diet) for 28 days. The heme-SCP diet seemed to restrain weight gain till day 14, but the mice gained weight again later, showing no significant differences in weight. However, the heme-SCP-fed mice had stiffer and oilier bodies compared with those of the control mice, which had flabby bodies and dull coats. When mice were dissected at day 10, the obese mice fed with heme-SCP exhibited a reduction in subcutaneous fat with an increase in muscle mass. The effect of heme-SCP on the obesity-associated dyslipidemia tended to be corroborated by the blood parameters (triglyceride, total cholesterol, and C-reactive protein) at day 10, though the correlation was not clear at day 28. Notably, the heme-SCP diet altered gut microbiota, leading to the proliferation of known anti-obesity biomarkers such as Akkermansia, Alistipes, Oscillibacter, Ruminococcus, Roseburia, and Faecalibacterium. This study suggests the potential of heme-SCP as an anti-obesity supplement, which modulates serum biochemistry and gut microbiota in high-fat diet-induced obese mice.
Keywords: Animals; Chickens; Diet, High-Fat; Dogs; Gastrointestinal Microbiome; Heme; Mice; Mice, Inbred C57BL; Mice, Obese; Obesity; Tissue Distribution; Heme-SCP; iron; lipid; microbiota; obesity